The research landscape of ferroptosis in neurodegenerative disease: a bibliometric analysis - Liu, Yun; Feng, Dan; Shui, Ling; Wang, Yu-jie; Yu, Li; Liu, Yu-qi; Tian, Jin-yong (Frontiers in Aging Neuroscience, 2024)
Background Ferroptosis, a newly proposed concept of programmed cell death, has garnered significant attention in research across different diseases in the last decade. Despite thorough citation analyses in neuroscience, there is a scarcity of information on ferroptosis research specifically related to neurodegenerative diseases. Method The Web of Science Core Collection database retrieved relevant articles and reviews. Data on publications, countries, institutions, authors, journals, citations, and keywords in the included studies were systematically analyzed using Microsoft Excel 2019 and CiteSpace 6.2.R7 software. Result A comprehensive analysis and visualization of 563 research papers on ferroptosis in neurodegenerative diseases from 2014 to 2023 revealed emerging research hotspots and trends. The number of annual publications in this field of study has displayed a pattern of stabilization in the early years of the decade, followed by a notable increase in the later years and peaking in 2023 with 196 publications. Regarding publication volume and total citations, notable research contributions were observed from countries, institutions, and authors in North America, Western Europe, and China. Current research endeavors primarily focus on understanding the intervention mechanisms of neurodegenerative diseases through the ferroptosis pathway and exploring and identifying potential therapeutic targets. Conclusion The study highlights key areas of interest and emerging trends in ferroptosis research on neurodegenerative diseases, offering valuable insights for further exploration and potential directions for diagnosing and treating such conditions.